Unsung heroes of the Lord of the rings : from the page to the screen - Porter, Lynnette R., 1957- (Praeger Publishers, 2005)
Most criticism of The Lord of the Rings trilogy emphasizes the most likely heroes in the tales: Aragorn, Frodo, Gandalf, and even Sam. From popular to scholarly literature, the women and smaller characters often go overlooked. But our notions of what makes a hero have altered since September 11, and sometimes the most unlikely people can come to embody all that we look up to and admire in a person. Here, Lynnette Porter examines what we mean when we talk about heroes, and for the first time illustrates the heroic qualities that can be found in the women and other beloved, though less-celebrated, characters in the The Lord of the Rings books and movies. She takes a critical look at the importance of literary and cinematic heroes in general, emphasizing the roles of Merry, Pippin, Galadriel, Eowyn, Arwen, Legolas, and Gimli, who can all be considered heroes despite their relatively smaller roles. She shows, ultimately, that our attraction to and celebration of heroes does not have to be limited to the leading man, but rather that women and youth often display essential characteristics of true heroes. Bringing together a discussion of both the books and the movies, Porter reveals for readers the heroic nature of several characters in The Lord of the Rings who have been ignored in terms of their status as heroes. Nevertheless, these female and youthful characters have received incredible popular acclaim and illustrate the shift in the way the Western movie-going public identifies and glorifies heroes. While other stars may have outshone the likes of Merry and Pippin, Arwen and Galadriel, Porter redirects the spotlight on these favorites of the books and movies to show us how the roles they play, the actions they take, and the behaviors they display are worthy of our praise and admiration. This unique and refreshing perspective adds dimension to our understanding of The Lord of the Rings phenomenon.